The Overreaction Effect in the Indian Stock Market - Tripathi, Vanita; Aggarwal, Shalini (Asian Journal of Business and Accounting, 2009)
This paper examines if there is any overreaction effect present in the Indian stock market, using the monthly closing adjusted prices of 500 stocks comprising S&P CNX 500 Equity Index over the period from March 1996 to March 2007 and the methodology in De Bondt and Thaler (1985), and Chan (1988). The findings reveal the presence of statistically significant but asymmetric overreaction effect in the Indian stock market. Contrarian investment strategy has been found to be economically feasible, generating abnormally positive returns on market-adjusted as well as risk-adjusted basis which are largely attributable to the extremely positive returns to loser stocks during the test period. These findings cast serious objections against the informational efficiency of the Indian stock market suggesting that investors can earn superior returns by making use of the information on past prices of securities.